2020
DOI: 10.1037/neu0000613
|View full text |Cite
|
Sign up to set email alerts
|

Detecting feigned traumatic brain injury with eye tracking during a test of performance validity.

Abstract: Objective: Eye-tracking is a promising technology to enhance assessment of performance validity. Research has established that ocular behaviors are reliable biomarkers of (un)conscious cognitive processes, and they have distinguished deceptive from honest responding in experimental paradigms. This study examined the incremental utility of eye-tracking on a clinical performance validity test (PVT) in distinguishing adults with verified TBI from adults coached to feign cognitive impairment. Method: Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Their results pointed to strategies used by simulators and cognitive processes that underlie the feigning of cognitive impairments. More recently, Kanser et al (2020) demonstrated that measuring eye behavior may enhance assessment of performance validity. Relying on previous literature on eye movements as reliable biomarkers of unconscious cognitive processes (Barry & Ettenhofer, 2016;Cook et al, 2012;Griffin & Oppenheimer, 2006;Kanser et al, 2017;Vrij et al, 2011), the authors examined the incremental utility of eye behavior on PVTs in discriminating between people who suffered Traumatic Brain Injury (TBI) and people coached to feign cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results pointed to strategies used by simulators and cognitive processes that underlie the feigning of cognitive impairments. More recently, Kanser et al (2020) demonstrated that measuring eye behavior may enhance assessment of performance validity. Relying on previous literature on eye movements as reliable biomarkers of unconscious cognitive processes (Barry & Ettenhofer, 2016;Cook et al, 2012;Griffin & Oppenheimer, 2006;Kanser et al, 2017;Vrij et al, 2011), the authors examined the incremental utility of eye behavior on PVTs in discriminating between people who suffered Traumatic Brain Injury (TBI) and people coached to feign cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…This was found to measure cognitive processes and showed initial promises for the detection of feigned cognitive impairment. Similarly, Kanser et al (2020) examined the incremental utility of eye tracking on a clinical PVT in distinguishing adults diagnosed with TBI from adults coached to feign cognitive impairment. Using eye tracking, the authors found that participants feigning TBI showed multiple signs of greater cognitive effort than both TBI patients and healthy comparisons, and they concluded that eye tracking may be an important complement to traditional accuracy scores on PVTs.…”
Section: Eye Tracking As Performance Validity Measurementioning
confidence: 99%
“…Nonparametric rank-based methods are frequently used particularly in the empirical or life sciences research disciplines (e.g., in psychology; see Kanser et al, 2020, and in medicine; see Han and Jung, 2018;Zimmermann et al, 2019). Basically, there might be at least two reasons for that: On the one hand, the fact that rank-based methods are also applicable to ordinal data renders them useful for analyzing qualityof-life scores, disease severity scales, or more generally, any rating or score of (scientific) interest that satisfies some order relation between its categories.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of a clinical group is especially important to the development of new indices designed to detect malingering. Laboratory designs that contrast only healthy adults instructed to be deceptive (TBI simulators) and healthy adults instructed to perform their best often yield results with much larger effects and different patterns than are observed for designs that include the clinical group of interest (Kanser et al, 2020(Kanser et al, , 2019Patrick et al, 2020).…”
mentioning
confidence: 99%
“…Biometrics yield psychophysiological markers that provide insight about effort and deception. Success in distinguishing true versus malingered memory test performance in TBI assessment has been demonstrated using biometrics such as reaction time (Kanser et al., 2019; Lupu et al., 2018; Patrick et al., 2020; Rose et al., 1998) and oculomotor gaze patterns during PVTs (Kanser et al., 2020; Tomer et al., 2020). Pupillary reactivity during testing is another promising avenue for investigation in biometrics.…”
mentioning
confidence: 99%